Retinal vessel oxygen saturation in healthy individuals. - Geirsdottir, Asbjorg; Palsson, Olafur; Hardarson, Sveinn Hakon; Olafsdottir, Olof Birna; Kristjansdottir, Jona Valgerdur; Stefánsson, Einar (Investigative Opthalmology & Visual Science, 2013)
We measured oxygen saturation in retinal vessels of healthy eyes to determine the effects of age, sex, and cardiovascular parameters, as well as the reliability of the measurements and topographic differences. The Oxymap T1 retinal oximeter is based on a fundus camera. It simultaneously captures retinal images at two different wavelengths and estimates retinal vessel oxygen saturation. Mean saturation of main retinal arterioles and venules was measured in 120 healthy individuals aged 18-80 years (median 47 years). Of the 120 participants 44 (37%) were male (49 years) and 76 (63%) female (44 years). Oxygen saturation was 92.2 ± 3.7% (mean ± SD) in retinal arterioles and 55.6 ± 6.3% in venules. No significant difference in oxygen saturation was found between left and right eyes. The inferotemporal quadrant had lower oxygen saturation in arterioles and venules (P < 0.0001). Arteriolar oxygen saturation was stable with age. Venular oxygen saturation in males decreased by 1.9 ± 0.6% (mean ± SEM) per 10 years of age (P = 0.003) and by 0.7 ± 0.4% in females (P = 0.068). Arteriovenous (AV) difference increased by 1.5 ± 0.5% per 10 years in males (P = 0.004) and 1.0 ± 0.4% (P = 0.007) in females. For every 10 mm Hg increase in ocular perfusion pressure, oxygen saturation in arterioles increased by 0.9 ± 0.4% (P = 0.024) and in venules by 1.2 ± 0.7% (P = 0.075). Retinal arteriolar oxygen saturation is stable in healthy individuals, while there is a significant decrease in venular oxygen saturation with age in males and a similar trend in females. AV difference increases significantly with age for both sexes. Our study provided normative data for spectrophotometric retinal oximetry in the Caucasian population. Prevention of Blindness Fund Landspitali-University Hospital Research Fund University of Iceland Research Fund Icelandic Center for Research (Rannis) Fund